2016
DOI: 10.5301/jabfm.5000258
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity Enhancement of Titanium Induced by Nd: Yag Laser Pulses

Abstract: It was concluded that the variation of the surface roughness, surface morphology, and oxidation level of the material has a direct effect on the cell adhesion rate to the surface of the titanium. Upon completion of the analysis, it is concluded that using a higher power and a lower dwelling time results in better bioactivity improvement than using higher dwelling times and lower powers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Structural difference of laser texturing samples leads to diverse surface properties(Radmanesh & Kiani, ; Rebollar et al, ; Vilhena et al, ), which will subsequently affect their biocompatibility. In the experiments, the elemental distribution of the polished and laser‐treated TC4 samples was examined by EDS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural difference of laser texturing samples leads to diverse surface properties(Radmanesh & Kiani, ; Rebollar et al, ; Vilhena et al, ), which will subsequently affect their biocompatibility. In the experiments, the elemental distribution of the polished and laser‐treated TC4 samples was examined by EDS.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed that the wettability was one of the main factors affecting cell proliferation and adhesion(Radmanesh & Kiani, ; Rebollar et al, ; Vilhena et al, ). Different surface‐texturing technologies have different effects on the surface wettability of materials.…”
Section: Discussionmentioning
confidence: 98%
“…Surface topography properties consist of three main characteristics: lay, roughness, and waviness. [12][13][14] The topographical properties of a material, particularly roughness, are very influential on cell attachment and cell behavior. 2,3 Laser treatment influences all properties of topography, particularly the roughness, surface profile, and oxidation of the treated material, which are closely examined in Sec.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidation directly affects the surface energy of the material, and hence with a higher oxidation, better cell adhesion is expected. 5,12,16 During laser irradiation, a plume with radial surface tension is created surrounding the heat-affected zone due to the temperature gradient caused by energy transfer. This vaporized plume (plasma) consists of nanoparticles, ions, and clusters that are created through the ablation of the material during laser irradiation.…”
Section: B Effects Of Laser Treatment-oxidation Levelmentioning
confidence: 99%
“…There are also many potential applications in biomedical engineering. It’s been proven that laser processing a metallic surface can significantly improve the biocompatibility in the ablated area and living cells can adhere better to the surface [ 9 13 ] whereas, the heat affected zone becomes less biocompatible and cells will avoid that area [ 14 ]. Therefore, the growing pattern of the cells can be controlled by laser processing of the surface which has many potential applications in biomedical engineering.…”
Section: Introductionmentioning
confidence: 99%